2009
DOI: 10.1177/070674370905400303
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Meta-cognitive Dimensions of Psychoses

Abstract: T he cognitive approach distinguishes between the normality of psychotic experiences and the later appraisal and (sub)cultural context making sense of the experience and emotional reaction to the thoughts. A key claim here is that the symptoms of a psychotic experience, for example, voice hearing, delusions, persecutory ideas, and dissociations, are all phenomena that have been experienced at one time by most people without psychosis. What makes the symptoms more persistent in the case of psychosis is a peculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Our results are consistent with the view that 'fantasy' converges with delusionproneness, cognitive-perceptual aberrations and disorganized features [73]. Pronounced 'fantasy' may indicate some vulnerability for schizophrenia [74], but might represent a reasoning style like cognitive slippage or perceptual immersion that is normally distributed in the population and pronounced in at-risk populations, and but has to interact with attributional biases in order to result in psychosis [75]. However, 'fantasy' was questioned to represent an aspect of cognitive empathy but was rather related to emotionality [76], suggestibility, dissociative experiences [77,78] or constructs like 'transliminality' [79].…”
Section: Specificity Of Social-cognitive Deficitssupporting
confidence: 89%
“…Our results are consistent with the view that 'fantasy' converges with delusionproneness, cognitive-perceptual aberrations and disorganized features [73]. Pronounced 'fantasy' may indicate some vulnerability for schizophrenia [74], but might represent a reasoning style like cognitive slippage or perceptual immersion that is normally distributed in the population and pronounced in at-risk populations, and but has to interact with attributional biases in order to result in psychosis [75]. However, 'fantasy' was questioned to represent an aspect of cognitive empathy but was rather related to emotionality [76], suggestibility, dissociative experiences [77,78] or constructs like 'transliminality' [79].…”
Section: Specificity Of Social-cognitive Deficitssupporting
confidence: 89%
“…Indeed, it has been demonstrated that in such situations, healthy subjects tend to perceive illusory patterns, creating regularities where there are none, and providing superstitious or conspiratorial explanations for ambiguous scenarios. 14 These observations resemble the early features of psychosis, including sense of change and feeling of strangeness, 15, 16, 17 search for explanation, 18, 19 apophenia 20 and jumping to conclusions. 21, 22 …”
Section: Introductionmentioning
confidence: 71%
“…The study's fi ndings also imply that proneness to double- think at least partly mediates the relationship between defi cient reality testing and the formation of conspiratorial beliefs; this inference warrants specifi c empirical scrutiny. More generally, research is needed on the possible role in conspiratorial ideation of other cognitive processes associated with the formation of delusions (see O'Connor, 2009 ). On the other hand, we must stress that the small eff ect size of the present fi nding cautions against any overstatement of the study's usefulness.…”
Section: Discussionmentioning
confidence: 99%